1998
DOI: 10.1177/000348949810700505
|View full text |Cite
|
Sign up to set email alerts
|

Verrucous Carcinoma of the Larynx

Abstract: Verrucous carcinoma is a well-differentiated squamous cell carcinoma with minimal cytologic atypia. Characteristically, the surface shows papillary fronds with prominent hyperkeratosis. Its benign appearance makes diagnosis difficult and often delays treatment. This is a review of 52 histologically confirmed cases of verrucous carcinoma of the larynx treated at the Mayo Clinic between 1960 and 1987. The follow-up ranged from 2 to 304 months. The most common primary treatment modality was surgery. Two patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 17 publications
4
34
0
1
Order By: Relevance
“…Local tumor control with no local recurrences was achieved in 11 of 12 of our patients and the toxicity of combined treatment was acceptable. This result compares favorably with the results of surgical series and even more with those of radiotherapy series, in which local recurrence rates in the range of 0%-29% [4][5][6][7][8] and 38%-46% [5,[9][10][11], respectively, were reported. However, in the case of rare clinical entities like VC, one should be aware that comparison of effectiveness of different treatment modalities is problematic, primarily because, in pertinent studies, broad time intervals are usually covered, including a bias because of substantial improvements in equipment and treatment techniques.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Local tumor control with no local recurrences was achieved in 11 of 12 of our patients and the toxicity of combined treatment was acceptable. This result compares favorably with the results of surgical series and even more with those of radiotherapy series, in which local recurrence rates in the range of 0%-29% [4][5][6][7][8] and 38%-46% [5,[9][10][11], respectively, were reported. However, in the case of rare clinical entities like VC, one should be aware that comparison of effectiveness of different treatment modalities is problematic, primarily because, in pertinent studies, broad time intervals are usually covered, including a bias because of substantial improvements in equipment and treatment techniques.…”
Section: Discussionsupporting
confidence: 78%
“…According to the presented results, the combined approach appears to compete favorably with surgery as a preferred treatment modality in this disease, which resulted in local failure rates of up to 29% [4][5][6][7][8]. The administration of chemotherapy during the course of irradiation seems to compensate successfully suboptimal effectiveness of irradiation in VC.…”
Section: Yes Yes Yesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report suggests that dedifferentiation can occur not only after radiation, but also before treatment and after surgery alone [39]. In 1998, the Mayo Clinic reviewed 52 cases of laryngeal verrucous carcinoma and concluded that radiotherapy can be used effectively as an adjunct to surgical resection to preserve laryngeal function [40]. Only one of four patients in this series treated with radiotherapy to control residual disease developed a recurrence, and none showed dedifferentiation or distant metastasis after radiation treatment.…”
Section: Discussionmentioning
confidence: 92%
“…En una serie de 52 casos de carcinoma verrucoso de laringe, dos pacientes tuvieron recurrencia local de su enfermedad y en el estudio histológico se demostró una desdiferenciación 9 . Para la adecuada evaluación de estos pacientes resulta imprescindible un buen diagnóstico histológico.…”
Section: Revisión Bibliográficaunclassified